The New Paradigm of Islamic Economics: Challenges and Solutions from the Perspective of M. Amin Abdullah - Rodyah Awallul Rohmah; Mega Kilawati; Helmi Syaifuddin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic economics has shown rapid development in recent years. However, behind the progress achieved, there are still a number of challenges and obstacles, both in terms of theory and practical implementation. This study aims to explore Amin Abdullah's views on the challenges faced by Islamic economics and the solutions he offers. This research uses a qualitative approach with a literature study method. The results show that the challenges and problems in Islamic economics according to Prof. Amin Abdullah include various factors that affect the growth of sharia-based economic systems, both in Indonesia and globally. Prof. Amin Abdullah proposes various solutions to overcome the challenges and problems faced by Islamic economics today. One of the main solutions he offers is the integration-interconnection paradigm in education and science development. Prof. Amin Abdullah argues that to face the challenges of modernity, Muslims need to combine religious science with general science.